2007
DOI: 10.1007/s00542-006-0348-z
|View full text |Cite
|
Sign up to set email alerts
|

MEMS design and fabrication of an electrostatic vibration-to-electricity energy converter

Abstract: This paper presents a micro electrostatic vibration-to-electricity energy converter based on the micro-electromechanical system. For the 3.3 V supply voltage and 1 cm 2 chip area constraints, optimal design parameters were found from theoretical calculation and Simulink simulation. In the current design, the output power is 200 lW/cm 2 for the optimal load of 8 MW. The device was fabricated in a silicon-on-insulator wafer. Mechanical and electrical measurements were conducted. Residual particles caused shortag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 7 publications
(11 reference statements)
0
27
0
Order By: Relevance
“…In the calculation of C max and C min for the out-ofplane gap closing structure, reference can be made to Eqs. (13) and (14), respectively. In particular, in the calculation of C min , the g 0 value is treated to be equivalent to the g i value in the corresponding in-plane gap closing structure.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In the calculation of C max and C min for the out-ofplane gap closing structure, reference can be made to Eqs. (13) and (14), respectively. In particular, in the calculation of C min , the g 0 value is treated to be equivalent to the g i value in the corresponding in-plane gap closing structure.…”
Section: Resultsmentioning
confidence: 98%
“…If the in-plane overlap and in-plane gap closing converters were to be compared, it can be observed that the maximum capacitance of the in-plane overlap converter is very similar to the minimum capacitance of the in-plane gap closing structure. By considering sample comb finger dimensions from the work done by Chiu et al, where A 0 = 1200 m × 200 m, t = 0.05 m, g 0 = 35 m, ε Si 3 N 4 = 7, ε 0 = 8.854 × 10 −12 Fm −1 [14], the maximum capacitance for one set of combs for the in-plane overlap converter will be 0.122 pF, and the minimum capacitance can be treated to be zero. On the other hand, for the same comb finger dimensions, the maximum capacitance will be 0.149 nF and the minimum capacitance will be 0.122 pF for one comb set in the in-plane gap closing generator.…”
Section: Device Structure and Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical vibration-to-electricity energy conversion technology is based on three mechanisms, namely electromagnetic inductive conversion [8,[20][21][22][23], electrostatic capacitive conversion [24][25][26][27][28] and piezoelectric conversion [29][30][31][32]. Electromagnetic energy conversion is based on Faraday's law of induction.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of the electrostatic energy harvester is the easy integration into electronic devices by MEMS 1 process technologies using a process similar to integrated accelerometer manufacturing [43,70]. The down scaling of the energy harvester, thus obtaining a smaller size, is easier than for the other types of vibration energy harvesters.…”
Section: Electrostatic Energy Harvestermentioning
confidence: 99%